Microbiological analysis of contact lens cases: impact of the hospital environment - Bôas,Vinicius Targa Villas (2018)
ABSTRACT Purpose: The aim of this study was to analyze the bacterial and fungal microbiota found in contact lens cases among two groups of patients to correlate the data on the habits of contact lens users and to evaluate whether there is a difference in the culture results between users of ridged and nonridged contact lens cases. Methods: Two groups (35 patients per group) were included, consisting of hospital workers and those who had not visited a hospital in the past 30 days, and a questionnaire regarding epidemiological data and habits related to contact lens and lens case use was administered. In addition, 140 samples collected from the right and left compartments of each lens case by swabbing the bottom of the wells were tested using bacterioscopy as well as fungal and bacterial cultures via computerized identification of the species. Results: No fungal growth was identified in any of the 70 contact lens cases; however, bacteria were found in 39 cases, and there was no statistical difference between the groups. Most bacteria (>85%) were gram-negative bacilli. Contamination inone compartment of the contact lens case elevated the risk of contamination of the other side (>80%). Moreover, contamination was statistically higher in the ridged cases than in nonridged cases (p=0.0149). Conclusion: The types of bacteria contaminating the cases are generally not seen in eye diseases associated with contact lens use, suggesting that other decisive variables are involved in eye infection from a contaminated lens or case. Fungal contamination of contact lens cases appears to be an exception. Ridged cases are commonly used by contact lens wearers and present a potential risk to eye health. In addition, the results of bacterial tests between hospital workers and those who did not visit a hospital were not significantly different.